Chirality reversal, enhancement and transfer by pH-adjusted surfactant assembly. Issue 97 (24th November 2020) - Zhou, Zhanglang; Zhou, Jin; Chen, Lan; Zhao, Qian; Zhang, Chun; Ge, Guanglu
Abstract : Chirality can be reversibly reversed via acid–base regulation. Abstract : The controllable chirality reversal and enhancement at a supramolecular level is crucial for the synthesis and applications of circularly active materials, which has been achieved by a pH-adjusted amphiphilic chiral surfactant assembly approach, and reveals the relationship between the chirality behavior and its assembly morphology in a non-covalent interaction regime and its ability to transfer chirality from chiral molecules to achiral ones under appropriate conditions.